Analisis Potensi dan Pegembangan Objek Wisata Alam Pulau Paniki di Desa Kulu Kec. Wori Kab. Minahasa Utara - Margaretha N Warokka; Sicilia Selvy Panelewen (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
The purpose of this research is, first, provide input to the government in managing the potential of natural tourism objects in Kulu Village and developing them so that more tourists come to this area thereby increasing regional income. Second, involve business actors as tourism object developers in building and equipping existing facilities so that the level of tourist visits increases which has an impact on community economic growth and regional income. The method used in this research is, using a qualitative descriptive method. Descriptive research was conducted to obtain an overview of tourism planning so that the potential and development of natural tourism objects in Kulu Village, Wori District can be carried out according to tourism characteristics and can produce a tourism development strategy model. Where the data collection methods used in this study are as follows: First through interviews, namely to the Village Apparatus, and tourism business people. Second, observation, the data collection method used in addition to the interview method is the observation method, which directly goes down to the field to observe the potential existence and development of tourist objects and tourists in this area. Third, documentation. Keywords: Analysis, Strategy, Development